Prevalence of and Factors Associated with Adverse Maternal Obstetrical Events Among Teenage Mothers Delivering in a Tertiary Referral Hospital in Southwestern Uganda - Ngonzi, Joseph; Birungi, Wilson; Byamukama, Onesmus; Kamugisha, Arnold; Asiimwe, Josephine; Ntaro, Moses; Nambozi, Grace; Tibaijuka, Leevan; Tushabomwe-Kazooba, Charles (Cureus, 2024)
Introduction: Many female teenagers in low-resource settings conceive, of which half are unplanned and end in many deaths in sub-Saharan Africa, accounting for the majority of the cases. Teenage pregnancy is associated sometimes with poor maternal, newborn, and child deaths. Objectives: The aim of the study was to determine the prevalence, maternal obstetric outcomes, and factors associated with poor maternal obstetric outcomes among teenage mothers delivering at Mbarara Regional Referral Hospital. Methods: This was a cross-sectional study carried out in a maternity ward at Mbarara Regional Referral Hospital, where 9,200 mothers deliver annually. All the women coming in for the delivery of their babies were consecutively approached for inclusion in the study. The women were enrolled in the post-delivery ward after delivery and interviewed with pretested questionnaires to capture the sociodemographic, obstetric, and medical profiles of the mothers. Factors were significant if the p-value was <0.05. Results: Out of the 327 participants, the majority were rural dwellers (68.5%), married (75.8%), attained primary education (69.4%), had not used contraception (89%), and had had a planned pregnancy (63.3%). The prevalence of adverse maternal obstetrical events was 59.9%. The HIV-positive rate was 4.9%, and about half of the participants had delivered by cesarean section (41.6%). The participants' mean age was 18.4 years and SD 1.1. The mean number of antenatal care contacts attended was 4.59 and SD 1.9. The adverse maternal outcomes included episiotomy (30.9%), perineal tear (18.7%), premature rupture of membranes (10.1%), placenta abruption (5.2%), and pre-eclampsia/eclampsia (4%). Having a cesarean delivery was found to significantly reduce the occurrence of adverse maternal obstetric events among the participants by 97% (adjusted odds ratio (aOR) (95% CI) of 0.03 (0.02-0.06), p-value <0.001). Having a prior history of a miscarriage was significantly associated with the occurrence of adverse maternal obstetrical events among the participants (aOR (95% CI) of 6.55 (1.46-29.42), p-value 0.014). Conclusions: Slightly more than half of the teenage mothers had adverse maternal obstetrical outcomes, and a history of a miscarriage in previous pregnancies was significantly associated with adverse maternal obstetrical outcomes. Having a cesarean delivery was found to significantly reduce the occurrence of adverse maternal obstetric events among the participants. Teenage mothers are at a high risk of adverse maternal obstetrical outcomes, and close antepartum and intrapartum surveillance is recommended.
Keywords: Uganda; Factors associated; Adverse maternal outcomes; Maternal child health; Teenage pregnancy